2017
DOI: 10.1093/cid/cix474
|View full text |Cite
|
Sign up to set email alerts
|

Management of Bacteriuria in Veterans Affairs Hospitals

Abstract: Gender, (male), n (%) 2065 (92.8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 21 publications
2
58
0
2
Order By: Relevance
“…Given the high mortality and poor outcomes associated with invasive fungal disease, this seems to be a logical first step. Inappropriate management of UTIs is not specific to yeast, as similar trends exist for bacterial UTIs (25). Although investigators have reported stewardship interventions focusing on the management of asymptomatic bacteriuria, the same is not true for candiduria (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high mortality and poor outcomes associated with invasive fungal disease, this seems to be a logical first step. Inappropriate management of UTIs is not specific to yeast, as similar trends exist for bacterial UTIs (25). Although investigators have reported stewardship interventions focusing on the management of asymptomatic bacteriuria, the same is not true for candiduria (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Specific vaccines recommended vary between jurisdictions, but commonly include pertussis and influenza. There are also new maternal vaccines in development, including group B streptococcus 3 and respiratory syncytial virus (RSV). 4 This highlights the fundamental and expanding role of the midwife in counselling parents about the importance of vaccination.…”
mentioning
confidence: 99%
“…Of interest, both PCV15 formulations elicited higher OPA GMTs and IgG GMCs than PCV13 to serotype 3, a serotype that is still associated with a significant burden of pneumococcal disease in children and older adults despite high uptake of PCV13 in children in many countries for several years. [42][43][44] Although serotype-specific OPA GMTs or IgG GMCs were observed to be numerically higher for a given study vaccine than the 2 other study vaccines, the clinical significance of such differences are unknown as no serotype-specific correlate of protection against pneumococcal disease has been established in adults. No clear underlying biological or chemical reasons were found and such differences could be due to chance alone given the number of comparisons tested between PCV15-A, PCV15-B and PCV13.…”
Section: Discussionmentioning
confidence: 99%